TELAAH FUNGSI PENDIDIKAN ISLAM - Anisa, Anisa; Nurbaya, Siti; Hermawansyah, Hermawansyah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
This study aims to examine the function of Islamic education from three main dimensions, namely ideological, social, and economic. The research method used is a literature study by collecting data from various primary and secondary literature sources, including relevant books, journals, and articles. The results show that ideologically, Islamic education plays a role in shaping beliefs, character, and morals based on monotheism. From a social perspective, Islamic education serves to instill moral values, justice, and brotherhood to build a harmonious society. Meanwhile, in economic terms, Islamic education prepares individuals to be competent, ethical, and able to contribute to the economic development of the community. Thus, Islamic education has a strategic role in shaping a generation that is faithful, knowledgeable, and productive, which can support the overall progress of society.